Photovoltaic Partial Shading Performance Evaluation With a DSTATCOM Controller - Bibhuti Bhusan Rath; Manoj Kumar Panda; Bhola Jha; Arobinda Dash; Surya Prakash; Ranjan Kumar Behera; Khalifa Al Hosani; Srinivasarao Tegala; Utkal Ranjan Muduli (IEEE Access, 2022)
A solar photovoltaic distribution static compensator (SPV-DSTATCOM) under partial shading condition (PSC) is studied using a single-stage, 3-phase grid-connected mode. Under PSC, the performance of the grid-connected SPV-DSTATCOM is studied, and issues such as active current sharing, reactive power control, and harmonic elimination are addressed. Rejection of DC offset with such PSC condition is an issue when using a conventional Proportional Resonant (PR) controller. As a result of this research, a new and improved PR (IPR)-based second-order generalized integrator (SOGI) has been developed that has unity gain at the fundamental frequency and greater DC offset rejection capability to address the PR controller shortcomings. The proposed controller’s performance is evaluated in both steady-state and dynamic conditions with varying loads and different PSC conditions. An experimental evaluation of the proposed controller’s design assumptions is also presented in the form of a comparison with both the PR controller and the adaptive PR controller.